2020
DOI: 10.1038/s41598-020-66247-8
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic and optical responses of a composite material comprising individual single-walled carbon-nanotubes with a polymer coating

Abstract: The composites and thin films comprising individual single-walled carbon nanotubes with a polymer coating (p-cnts) have been prepared and their electromagnetic responses have been studied in a wide range from low-frequency (25-10 7 Hz) up to the infrared region. In spite of the high volume fraction of the nanotubes (up to 3.3%), the polymer coating prevents direct p-CNT contacts and the formation of the percolation network in those composites, so that p-CNTs interact only via the electromagnetic coupling. ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…An experimental characterization was performed to investigate the effect of carbon nanotubes, micro carbon fibers, and Fe 3 O 4 nano particles on electromagnetic shielding effectiveness in the X-band frequency range (8)(9)(10)(11)(12). Overall, the Fe 3 O 4 nano particles have a major influence on the total shielding effectiveness as well as on the absorption.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An experimental characterization was performed to investigate the effect of carbon nanotubes, micro carbon fibers, and Fe 3 O 4 nano particles on electromagnetic shielding effectiveness in the X-band frequency range (8)(9)(10)(11)(12). Overall, the Fe 3 O 4 nano particles have a major influence on the total shielding effectiveness as well as on the absorption.…”
Section: Discussionmentioning
confidence: 99%
“…They reported excellent EMI SE values and they were attributed to the synergistic effects between Fe 3 O 4 , CNT and lignin. Shuba et al [12] investigated the electromagnetic response of a composite material consisting of single-walled carbon-nanotubes in a wide range from low-frequency (25-10 7 Hz) up to the infrared region. They reported that the real part of the permittivity of the p-CNT film in the terahertz range is competitive.…”
Section: Introductionmentioning
confidence: 99%